ABC Fractional Derivative for the Alcohol Drinking Model using Two-Scale Fractal Dimension. (6th June 2022) - Tul Ain, Qura; Sathiyaraj, T.; Karim, Shazia; Nadeem, Muhammad; Kandege Mwanakatwe, Patrick
Abstract : Drinking kills a significant proportion of individuals every year, particularly in low-income communities. An impulsive differential equation system is used to explore the effectiveness of activated charcoal in detoxifying the body after methanol poisoning. Our impression of activated charcoal is shaped by the fractional dynamics of the problem, which leads to speedy and low-cost first aid. The adsorption capacity of activated charcoal is investigated using impulsive differential equations. The ABC fractional operator's findings paint a more realistic image of first aid in public and primary health centers, which can assist to reduce methanol poisoning deaths. Numerical simulations are provided using generalized Adams–Bashforth–Moulton method (GABMM).